Audiovisual technology as a supporting instrument for the orientation of breast self-exam - Isaura Letícia Tavares Palmeira; Raimunda Magalhães da Silva; Marcos Venícios de Oliveira Lopes; Ana Fátima Carvalho Fernandes (Rev Rene)
One aimed at analyzing the use of educative videotape as a supporting instrument for the orientation of breast self-exam and early detection of breast cancer. Data collection was divided into four moments at which educative videotape was on the screen. Most of the participants ignored the disease, the methods for early detection and did not carry out breast self-exam. After the exhibition of the educative videotape, the participants seemed to be more confident to talk about the disease, mentioned three exams for early detection and answered the questions made about breast self-exam correctly. We noticed that the use of educative videotape facilitated the women’s apprenticeship and that it is necessary to encourage this population to practice breast self-exam from time to time.